Historiography of Peasant Awakening and Tribal Movements in Bihar (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The historians in general either oversimplified ignorantly or ignored deliberately the history of Peasant awakening and tribal movements, their genesis and growth, their components and nature, their ramifications and repercussions and so no, in spite of their distinctive historical potentialities and contribution to the nationalist struggle. The negligent attitude of historians towards peasant and tribal problems and protests may broadly be attributed to the dominant class motivations, and also to the non- application of scientific methodology in the field of historiography of modern Bihar.Compared to Bengal and Maharashtra, the middle class in Bihar had a belated emergence in different socio-economic conditions.